To repair or not to repair: a case report of atrioventricular groove hematoma during mitral valve surgery - Hiroshi Nagamine; Yusuke Date; Takeshi Takagi; Yushi Kawase (Journal of Cardiothoracic Surgery, 2019)
Abstract Background Atrioventricular groove hematomas during mitral valve surgery range from simple hematomas to complex atrioventricular disruptions that cause frank rupture with massive bleeding and subsequent mortality. A small or moderate-sized hematoma is reported to be present in the left atrioventricular groove in 10 to 30% of all patients immediately after mitral valve replacement. Despite the fact that atrioventricular groove hematomas are inherently unstable and unpredictable, conservative strategies are recommended due to the high mortality associated with additional surgical repair. Such conservative strategies, however, would not resolve the potential risk of rupture, and there also appears to be a certain degree of uncertainty to be overcome using the current advances in cardiac surgery. Case presentation We present a case of atrioventricular hematoma during double valve replacement which was treated with conservative management. A left ventricular pseudoaneurysm developed after surgery, but spontaneously resolved completely within six months. After reflecting on our case, we developed a check sheet, including the anesthesiologist’s transesophageal echocardiography findings, for reasonable intraoperative decision-making regarding conservative management vs. additional surgical repair. Our check sheet helps organize the pathophysiological understanding of the injury and integrates partial findings from complementary viewpoints, and can be used to accurately assess intense situations and develop a common understanding among surgical team members. Conclusions Our case involved an atrioventricular groove hematoma that occurred during mitral valve surgery and caused a left ventricular pseudoaneurysm. Conservative strategies yielded positive results. We hope our experience and original check sheet will be of value to surgical teams facing similar situations.